Perancangan Sistem Informasi Geografis Pariwisata Pasaman Barat Berbasis Android Menggunakan Metode Haversine - Sugeng Purwantoro Edy Suranta G.S (Jurnal Komputer Terapan, 2021)
Tourism is an activity that is mostly carried out by the community today which aims to find a new atmosphere outside of daily routine activities. There are quite a lot of tourist destinations in Sumatra and one of them is a tourist location in West Pasaman Regency. However, many tourist objects are not known by visiting tourists, due to the lack of available tourist attraction information. Geographic Information System (GIS) can provide location information of a place, which can be used to display the location of tourist objects needed by tourists. The design of this system provides distance estimation calculations and recommendations for the closest distance locations using the Haversine method which functions to calculate the distance between two points. The system is designed on the android platform, MySQL database and PHP programming language. Tests using White Box, Black Box, and comparison testing with Google Maps Distance. In the White Box testing on the Haversine Formula program code and the tourist display program code, the results obtained are Cyclomatic Complexity 1 and 2 values, it is concluded that the program code has a simple risk level and without much risk so that it is easy to maintain and test the program flow. Black Box testing concluded that the functionality of the system is running well, in the analysis of the comparison test obtained an accuracy value of 100% and it is concluded that the calculation results are the same as Google Maps Distance